Neobacillus endophyticus sp. nov., an endophytic bacterium isolated from Selaginella involvens roots. Issue 3 (23rd March 2021) - Jiang, Lingmin; Lee, Myoung Hui; Jeong, Jae Cheol; Kim, Dae-Hyuk; Kim, Cha Young; Kim, Suk Weon; Lee, Jiyoung
Abstract : A Gram-stain-positive, facultatively anaerobic, rod-shaped, endospore-forming, oxidase-positive, and catalase-negative strain designated as BRMEA1 T was isolated from the surface-sterilized Selaginella involvens roots. Growth of strain BRMEA1 T was found to occur at pH 6.0–8.0 (optimum, pH 7.0), 15–50 °C (optimum, 25–30 °C) and in the absence of NaCl. Phylogenetic analysis based on 16S rRNA gene sequences indicated that strain BRMEA1 T formed a lineage within the genus Neobacillus (family Bacillaceae ) and showed the highest sequence similarity to Neobacillus drentensis DSM 15600 T (98.3 %) and Neobacillus fumarioli KCTC 13885 T (98.2 %), and less than 98.2 % 16S rRNA gene sequence similarity to the other members of the genus Neobacillus . Whole-genome analysis of strain BRMEA1 T comprised a circular chromosome (5 632 809 bp in size) with 38.5 mol% G+C content. Digital DNA–DNA hybridization analyses revealed that strain BRMEA1 T showed 20.5 and 22.0% genomic DNA relatedness with the closest species, N. drentensis DSM 15600 T and N. fumarioli KCTC 13885 T, respectively. The whole-genome sequence of strain BRMEA1 T showed the presence of 11 specific conserved signature indels for the genus Neobacillus . The major cellular fatty acids (>10 %) of strain BRMEA1 T were found to be iso-C15 : 0 and anteiso-C15 : 0, while the major polar lipids were found to be diphosphatidylglycerol, phosphatidylethanolamine and phosphatidylglycerol. Polyphasic analysis results revealed that BRMEA1 T represents a novel species of the genus Neobacillus, with the proposed name Neobacillus endophyticus sp. nov. The type strain is BRMEA1 T (=KCTC 43208 T =CCTCC AB 2020071 T ).